Self-nanoemulsifying system (SNES) enhanced oral bioavailability of boswellic acids. (January 2018) - Ting, Yuwen; Jiang, Yike; Zhao, Shuqi; Li, Colin C.; Nibber, Traj; Huang, Qingrong
Highlights: Self-nanoemulsification is effective in enhancing the bioavailability of boswellic acids. The particle sizes are stable against wide range of pH values. The degree of emulsification is optimum at 70% of water. The bioaccesibility of boswellic acid is much higher when being encapsulated. Abstract: Boswellia serrate gum resin extract is a potent anti-inflammatory agent that is widely used in ancient and modern medicinal systems. However, the efficacy of this bioactive ingredient is questionable due to its poor oral bioavailability. In this work, self-nanoemulsifying system (SNES) was used to enhance the systemic concentration of boswellic acids. The systemic concentrations of 11-keto-β-boswellic acid (KBA) and acetyl-11-keto-β-boswellic acid (AKBA), the most bioactive components of boswellic acids, were used as indicators to evaluate the efficiency of self-emulsifying system. In the study of lipolysis, the aqueous solubility and bioaccessibility of KBA and AKBA were increased by 2.7 and 2.3 folds, respectively. From the in vivo pharmacokinetic study, SNES triggered a significant increase in the oral bioavailability of KBA and AKBA by 2.2 and 2.0 times higher than the bulk oil suspension, respectively. Therefore, SNES with superior storage stability is an effective oral formulation to enhance bioavailability of boswellic acids.